Prediction of gradient retention data for hydrophilic interaction liquid chromatographic separation of native and fluorescently labeled oligosaccharides - Vaňková, Nikola; Česla, Petr (Journal of chromatography. A, 2017)
In this work, we have investigated the predictive properties of mixed-mode retention model and oligomeric mixed-mode model, taking into account the contribution of monomeric units to the retention, in hydrophilic interaction liquid chromatography. The gradient retention times of native maltooligosaccharides and their fluorescent derivatives were predicted in the oligomeric series with number of monomeric glucose units in the range from two to seven. The maltooligosaccharides were separated on a packed column with carbamoyl-bonded silica stationary phase and 15 gradient profiles with different initial and final mobile phase composition were used with the gradient times 5; 7.5 and 10min. The predicted gradient retention times were compared for calculations based on isocratic retention data and gradient retention data, which provided better accuracy of the results. By comparing two different mobile phase additives, the more accurate retention times were predicted in mobile phases containing ammonium acetate. The acidic derivatives, prepared by reaction of an oligosaccharide with 2-aminobenzoic acid or 8-aminonaphthalene-1,3,6-trisulfonic acid, provided more accurate predictions of the retention data in comparison to native oligosaccharides or their neutral derivatives. The oligomeric mixed-mode model allowed prediction of gradient retention times using only one gradient profile, which significantly speeded-up the method development.
Keywords: ortoaminobenzoáty; Silicon Dioxide; Fluorescent Dyes; Hydrophilic interaction liquid chromatography; Gradient elution; Prediction; Mixed-mode retention model; Chromatography, Liquid; fluorescenční barviva; ortho-Aminobenzoates; Oligosaccharides; oligosacharidy; Naphthalenes; oxid křemičitý; naftaleny; Oligomers; chromatografie kapalinová; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions